Preparation method and application of silicon carbide-loaded carbon-coated cobalt composite material

CN119565615AInactive Publication Date: 2025-03-07吉盛微(武汉)新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411001715.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

[0008]针对现有技术的不足,本发明提供了一种碳化硅负载碳包覆钴系复合材料的制备方法及其应用,解决了钴金属催化剂在使用过程中催化效率低、稳定性差及钴离子浸出率高的问题

Benefits of technology

[0027] 1. The present invention adopts a technical solution for carbon-coated cobalt-based catalyst supported by silicon carbide. By calcining molten salt on the basis of CoZn-Z IF material, a unique carbon-coated structure is formed, which significantly improves the catalytic performance. The technical effect of basically completely degrading antibiotics within 2 minutes was achieved. Compared with the problem of low efficiency of cobalt catalysts in degrading antibiotics in the prior art, the disadvantage of insufficient catalytic efficiency is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565615A_ABST
    Figure CN119565615A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalytic materials, and discloses a preparation method of a silicon carbide-loaded carbon-coated cobalt composite material, which comprises the following steps: respectively dissolving cobalt salt and zinc salt in methanol, uniformly dispersing, mixing, adding dimethylimidazole and cetyltrimethylammonium bromide, and treating reaction liquid A at normal temperature to obtain powder I; fully grinding the powder I and alkali-etched silicon carbide powder together, adding into methanol, and treating the reaction liquid B at normal temperature to obtain powder II; and uniformly mixing the powder II with mixed molten salt of ZnCl2 and KCl according to a mass ratio of 1: 1, fully grinding, heating and calcining in a protective atmosphere, performing hydrochloric acid leaching treatment, and treating the reaction solution C to obtain the silicon carbide-loaded carbon-coated cobalt composite material. By adopting the technical scheme that the formation of a carbon coating structure is promoted through a fused salt calcination process in the preparation process, the technical effect that the cobalt metal leaching rate is greatly reduced while the catalytic efficiency is guaranteed is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a method for preparing a silicon carbide-loaded carbon-coated cobalt-based composite material and application thereof. Background Art

[0002] Silicon carbide (SiC) crystals are composed of carbon-silicon tetrahedrons, with atoms bonded by four-sided sp3 hybridization to form a strong covalent bond compound. Silicon carbide has unique chemical and physical properties, such as hardness and mechanical stability at high temperatures, good thermal conductivity and low thermal expansion coefficient, as well as strong corrosion resistance and oxidation resistance. These properties make silicon carbide an ideal substitute for traditional proppants in many catalytic conversion processes. Silicon carbide has a rough surface and a high-order mesoporous structure, which gives it a high specific surface area and excellent mesoporous / macroporous properties, further enhancing its application value in catalysts.

[0003] The support has a great influence on the performance of the catalyst. A support with a high specific surface area can improve the distribution of active centers, balance the acidity and alkalinity of the catalyst surface, and improve the stability of the catalyst. There are many examples of silicon carbide as a catalyst support material. For example, the 2.5Ru / silicon carbide catalyst shows good catalytic stability at 723K, and there is no obvious sintering deactivation phenomenon due to the interaction between the metal and the support. In addition, the Co / SiC catalyst shows high selectivity and reusability in the Fischer-Tropsch synthesis reaction.

[0004] Cobalt catalysts have developed rapidly in recent years due to their high cost-effectiveness. In the past few decades, cobalt-based catalysts have been mainly used in the fields of energy and environment, so much so that the European Union has listed it as one of the important raw materials. The special catalytic activity of cobalt is mainly attributed to its partially filled d orbitals. Cobalt exists not only in elemental form, but also in Co 2 + and Co 3 + oxidation state, which makes it easier to combine with other elements or supports to form composite materials.

[0005] The carrier effect of Co-based catalysts is very obvious. The carrier can provide a high specific surface area for the dispersion of active components, improve the anti-sintering ability, the mass transfer and diffusion rate of reactants and products, and stabilize the active phase. In addition, the interaction between the metal and the carrier will produce an interfacial catalytic effect, and the catalytic reaction performance can be improved by regulating the metal-carrier interaction.

[0006] In order to increase the effective catalytic surface area, expose more active sites and selectively expose the most active catalytic centers, researchers have explored many nanostructures of cobalt and cobalt-based compounds. However, these nanostructures have a difficult problem to solve during the catalytic degradation process, namely the leaching of cobalt metal ions. According to China's "Surface Water Environmental Quality Standard" (GB3838-2002), the maximum concentration level of cobalt in surface water is 1.0 mg / L. Therefore, how to prepare a catalytic material with high catalytic efficiency, strong stability and low cobalt metal leaching rate is currently a key problem.

[0007] Therefore, the present invention proposes a preparation method of a silicon carbide-loaded carbon-coated cobalt-based composite material and its application to solve the deficiencies of the prior art. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a method for preparing a silicon carbide-loaded carbon-coated cobalt-based composite material and its application, which solves the problems of low catalytic efficiency, poor stability and high cobalt ion leaching rate of cobalt metal catalysts during use.

[0009] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a silicon carbide-loaded carbon-coated cobalt-based composite material, comprising the following steps:

[0010] (1) dissolving cobalt salt and zinc salt in methanol respectively, dispersing them uniformly, adding dimethyl imidazole and hexadecyl trimethyl ammonium bromide after mixing, stirring them ultrasonically at room temperature for 20 to 30 hours, maintaining the temperature of the reaction solution A at 25° C., and treating the reaction solution A to obtain a powder 1;

[0011] (2) grinding the powder 1 and the alkali-etched silicon carbide powder in step (1) together, adding them into methanol, stirring them continuously at room temperature for 1 to 2 hours, and then hydrothermally reacting them at 150 to 180° C. for 10 to 12 hours, and treating the reaction liquid B to obtain powder 2;

[0012] (3) The powder 2 described in step (2) is mixed with ZnCl 2 The mixed molten salt of KCl and SiC1 is uniformly mixed in a mass ratio of 1:1, fully ground, calcined at a high temperature under a protective atmosphere, and then treated with hydrochloric acid to obtain a carbon-coated cobalt-based composite material supported by silicon carbide.

[0013] Preferably, the cobalt salt is Co(NO 3 ) 2 6H 2 O, zinc salt is Zn(NO 3 ) 2 6H 2 O.

[0014] Preferably, the processing of the reaction liquid A comprises filtering the reaction liquid, washing the obtained filter cake with deionized water and methanol in sequence, and vacuum drying to obtain the powder 1.

[0015] Preferably, the mass ratio of the cobalt salt, the zinc salt and the dimethylimidazole is 1:10-12:12-15, and the ratio of the cobalt salt to methanol is 1 g:150 mL-200 mL.

[0016] Preferably, the stirring time in step (2) is 2 hours, the temperature is 25°C, and the hydrothermal reaction time is 12 hours, the temperature is 180°C.

[0017] Preferably, the treatment of reaction liquid B comprises filtering the reaction liquid, washing the obtained filter cake with deionized water and methanol in sequence, and vacuum drying to obtain powder 2.

[0018] Preferably, the molten salt is ZnCl 2 and KCl in a mixture in a mass ratio of 2:1; and a mass ratio of the second powder to the molten salt of 1:1.

[0019] Preferably, the protective atmosphere during the calcination process is a nitrogen atmosphere or an argon atmosphere, the heating rate is 2 to 5°C / min, the calcination time is 2 to 3 hours, and the temperature is 950 to 1050°C.

[0020] Preferably, the hydrochloric acid pickling comprises pickling with 0.5M hydrochloric acid at 60-80°C for 2-3 hours.

[0021] Preferably, the silicon carbide-loaded carbon-coated cobalt-based composite material is used to treat organic pollutant wastewater, wherein the silicon carbide-loaded carbon-coated cobalt-based composite material is dispersed into the organic pollutant wastewater, and persulfate is added to catalytically degrade the organic pollutants, wherein the organic pollutants are one or a mixture of two or more of norfloxacin, tetracycline, and bisphenol A.

[0022] Preferably, the silicon carbide-supported carbon-coated cobalt-based composite material is used in the catalytic degradation of antibiotics, especially antibiotics in sewage.

[0023] Preferably, the antibiotic is tetracycline.

[0024] Preferably, the concentration of the antibiotic in the aqueous solution containing the antibiotic is 20-40 mg / L; the ratio of the silicon carbide-supported carbon-coated cobalt-based composite material, potassium permonosulfate and the aqueous solution containing the antibiotic is 1:1:2L.

[0025] The invention provides a preparation method of a silicon carbide-loaded carbon-coated cobalt-based composite material and application thereof.

[0026] It has the following beneficial effects:

[0027] 1. The present invention adopts the technical solution of carbon-coated cobalt catalyst supported by silicon carbide, and forms a unique carbon-coated structure by molten salt calcination on the basis of CoZn-Z IF material, which significantly improves the catalytic performance. The technical effect of basically completely degrading antibiotics within 2 minutes is achieved. Compared with the problem of low efficiency of cobalt catalyst in degrading antibiotics in the prior art, the disadvantage of insufficient catalytic efficiency is solved.

[0028] 2. The present invention adopts a technical solution of promoting the formation of a carbon coating structure through a molten salt calcination process during the preparation process, achieving the technical effect of greatly reducing the leaching rate of cobalt metal while ensuring the catalytic efficiency. Compared with the problem of high leaching rate of cobalt ions in the use of cobalt catalysts in the prior art, the problem of potential pollution to the environment is solved.

[0029] 3. The present invention adopts the technical solution of adding silicon carbide as a carrier material during the preparation process, which not only increases the specific surface area of ​​the material and enhances the adsorption performance, but also improves the cyclic stability of the catalyst during the degradation process. The technical effect of maintaining efficient and stable catalytic performance under different temperature and pH conditions is achieved. Compared with the problem of poor stability of the catalyst in long-term use in the prior art, the defect of insufficient cyclic stability in practical applications is solved.

[0030] 4. The invention uses silicon carbide (SiC) as a carrier, giving full play to its excellent properties such as high temperature hardness, mechanical stability, good thermal conductivity and low thermal expansion coefficient, achieving the technical effect of improving the overall performance and adaptability of the catalyst. Compared with the problem of unstable performance of traditional catalyst carriers in harsh environmental conditions in the prior art, it solves the shortcoming of insufficient physical and chemical properties.

[0031] 5. The present invention reduces the environmental pollution of metals by developing a catalyst material with low cobalt ion leaching, and provides an environmentally friendly technical solution by efficiently degrading organic pollutants such as antibiotics. The technical effect of protecting the environment and reducing pollution is achieved. Compared with the problem of poor environmental friendliness of catalysts in the prior art, the defect of insufficient environmental performance is solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 XRD pattern of the carbon-coated cobalt-based catalyst material supported by silicon carbide prepared in Example 1

[0033] Figure 2 TEM image of the carbon-coated cobalt-based catalyst material supported by silicon carbide prepared in Example 1

[0034] Figure 3 SEM image of the cube-CoZn-Z IF material prepared in Comparative Example 6 without adding silicon carbide and calcining with molten salt

[0035] Figure 4 Comparison of the leaching amount of cobalt ions in the first catalytic degradation cycle (30 min) of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 6

[0036] Figure 5 This is a time degradation rate curve of tetracycline degradation under different temperature conditions for the carbon-coated cobalt-based catalyst material supported by silicon carbide prepared in Example 1

[0037] Figure 6 This is a time degradation rate curve of tetracycline degradation under different pH conditions by the silicon carbide supported carbon-coated cobalt-based catalyst material prepared in Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example:

[0040] Please see attached Figure 1 -Attached Figure 6 :

[0041] Embodiment 1:

[0042] Raw material dissolution:

[0043] Weigh 1.455 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0044] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0045] Solutions A and B were mixed and stirred uniformly, and then 0.05 g of cetyltrimethylammonium bromide (CTAB) was added to obtain a mixed solution D.

[0046] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0047] Mixed reaction:

[0048] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0049] Powder handling:

[0050] Weigh 0.5 g of powder 1 and 0.5 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 80 ml of methanol, and stir them continuously at room temperature for 2 hours to obtain a mixed solution E.

[0051] Hydrothermal reaction:

[0052] The mixed solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with deionized water / methanol for 3 times. Finally, the powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0053] Molten salt calcination:

[0054] Weigh 0.5g of powder 2 and 0.5g of ZnCl 2 The molten salts of MgCl (0.33 g) and KCl (0.17 g) were mixed evenly, ground thoroughly, and calcined in a tube furnace (temperature 950 °C, calcination time 3 h, heating rate 5 °C / min, nitrogen atmosphere), then washed with deionized water for 3 times, and finally dried in a vacuum drying oven at 60 °C for 24 h.

[0055] Acid leaching treatment:

[0056] The mixture was acid-leached at 80°C for 3 hours (0.5M HCl), the precipitate was collected by filtration using a vacuum pump, and washed three times with deionized water. Finally, the mixture was vacuum-dried in a vacuum drying oven at 60°C for 6 hours to obtain a silicon carbide-supported carbon-coated cobalt-based catalyst material.

[0057] Example 2 (Reducing SIC Ratio)

[0058] Preparation method:

[0059] Raw material dissolution:

[0060] Same as Example 1.

[0061] Mixed reaction:

[0062] Same as Example 1.

[0063] Powder handling:

[0064] Weigh 0.5 g of powder 1 and 0.25 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 50 ml of methanol, and stir them continuously at room temperature for 2 hours to obtain a mixed solution E.

[0065] Hydrothermal reaction:

[0066] Same as Example 1.

[0067] Molten salt calcination:

[0068] Same as Example 1.

[0069] Acid leaching treatment:

[0070] Same as Example 1.

[0071] Example 3 (reducing the Co ratio) Preparation method:

[0072] Raw material dissolution:

[0073] Weigh 0.728 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0074] The other steps are the same as in Example 1.

[0075] Mixed reaction:

[0076] Same as Example 1.

[0077] Powder handling:

[0078] Same as Example 1.

[0079] Hydrothermal reaction:

[0080] Same as Example 1.

[0081] Molten salt calcination:

[0082] Same as Example 1.

[0083] Acid leaching treatment:

[0084] Same as Example 1.

[0085] Comparative Example:

[0086] Comparative Example 1 (without adding silicon carbide)

[0087] Experimental process:

[0088] Raw material dissolution:

[0089] Weigh 1.455 g of Co(NO 3 ) 2 6H 2O was dissolved in 50 mL of methanol to obtain solution A.

[0090] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0091] Solutions A and B were mixed and stirred uniformly, and then 0.05 g (CTAB) was added to obtain a mixed solution D.

[0092] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0093] Mixed reaction:

[0094] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0095] Powder handling:

[0096] Weigh 0.5 g of powder 1, grind it thoroughly, dissolve it in 50 ml of methanol, and stir it continuously at room temperature for 2 hours to obtain solution E.

[0097] Hydrothermal reaction:

[0098] Solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with DIW / methanol for three times. Finally, powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0099] Molten salt calcination:

[0100] Weigh 0.5g of powder 2 and 0.5g of ZnCl 2 The molten salts of MgCl (0.33 g) and KCl (0.17 g) were mixed evenly, ground thoroughly, and calcined in a tube furnace (temperature 950 °C, calcination time 3 h, heating rate 5 °C / min, nitrogen atmosphere), then washed with deionized water for 3 times, and finally dried in a vacuum drying oven at 60 °C for 24 h.

[0101] Acid leaching treatment:

[0102] The mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), and the precipitate was collected by filtration using a vacuum pump, washed with deionized water for 3 times, and finally dried in a vacuum oven at 60° C. for 6 hours to obtain the composite material of Comparative Example 1.

[0103] Comparative Example 2 (without adding molten salt)

[0104] Experimental process:

[0105] Raw material dissolution:

[0106] Weigh 1.455 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0107] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0108] Solutions A and B were mixed and stirred uniformly, and then 0.05 g of cetyltrimethylammonium bromide (CTAB) was added to obtain a mixed solution D.

[0109] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0110] Mixed reaction:

[0111] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0112] Powder handling:

[0113] Weigh 0.5 g of powder 1 and 0.5 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 50 ml of methanol, and continue stirring at room temperature for 2 hours to obtain a mixed solution E.

[0114] Hydrothermal reaction:

[0115] The mixed solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with DIW / methanol for 3 times. Finally, the powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0116] Calcination:

[0117] Weigh 0.5 g of powder 2, grind it thoroughly, put it into a tube furnace for calcination (temperature 950°C, calcination time 3 hours, heating rate 5°C / min, nitrogen atmosphere), then wash it with deionized water 3 times, and finally dry it in a vacuum drying oven at 60°C for 24 hours.

[0118] Acid leaching treatment:

[0119] The mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), and the precipitate was collected by filtration using a vacuum pump, washed with deionized water for 3 times, and finally dried in a vacuum oven at 60° C. for 6 hours to obtain the composite material of Comparative Example 2.

[0120] Comparative Example 3 (without zinc)

[0121] Experimental process:

[0122] Raw material dissolution:

[0123] Weigh 1.455 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0124] Solution A was mixed with 0.05 g of cetyltrimethylammonium bromide (CTAB) and stirred to obtain a mixed solution D.

[0125] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0126] Mixed reaction:

[0127] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0128] Powder handling:

[0129] Weigh 0.5 g of powder 1 and 0.5 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 50 ml of methanol, and continue stirring at room temperature for 2 hours to obtain a mixed solution E.

[0130] Hydrothermal reaction:

[0131] The mixed solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with DIW / methanol for 3 times. Finally, the powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0132] Molten salt calcination:

[0133] Weigh 0.5g of powder 2 and 0.5g of ZnCl 2The molten salts of MgCl (0.33 g) and KCl (0.17 g) were mixed evenly, ground thoroughly, and calcined in a tube furnace (temperature 950 °C, calcination time 3 h, heating rate 5 °C / min, nitrogen atmosphere), then washed with deionized water for 3 times, and finally dried in a vacuum drying oven at 60 °C for 24 h.

[0134] Acid leaching treatment:

[0135] The mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), and the precipitate was collected by filtration using a vacuum pump, washed with deionized water for 3 times, and finally dried in a vacuum oven at 60° C. for 6 hours to obtain the composite material of Comparative Example 3.

[0136] Comparative Example 4 (without adding cobalt)

[0137] Experimental process:

[0138] Raw material dissolution:

[0139] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0140] Solution B and 0.05 g of cetyltrimethylammonium bromide (CTAB) were mixed and stirred to obtain a mixed solution D.

[0141] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0142] Mixed reaction:

[0143] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0144] Powder handling:

[0145] Weigh 0.5 g of powder 1 and 0.5 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 50 ml of methanol, and continue stirring at room temperature for 2 hours to obtain a mixed solution E.

[0146] Hydrothermal reaction:

[0147] The mixed solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with DIW / methanol for 3 times. Finally, the powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0148] Molten salt calcination:

[0149] Weigh 0.5g of powder 2 and 0.5g of ZnCl 2 The molten salts of MgCl (0.33 g) and KCl (0.17 g) were mixed evenly, ground thoroughly, and calcined in a tube furnace (temperature 950 °C, calcination time 3 h, heating rate 5 °C / min, nitrogen atmosphere), then washed with deionized water for 3 times, and finally dried in a vacuum drying oven at 60 °C for 24 h.

[0150] Acid leaching treatment:

[0151] The mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), and the precipitate was collected by filtration using a vacuum pump, washed three times with deionized water, and finally dried in a vacuum oven at 60° C. for 6 hours to obtain the composite material of Comparative Example 4.

[0152] Comparative Example 5 (Aerobic Calcination)

[0153] Experimental process:

[0154] Raw material dissolution:

[0155] Weigh 1.455 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0156] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0157] Solutions A and B were mixed and stirred uniformly, and then 0.05 g of cetyltrimethylammonium bromide (CTAB) was added to obtain a mixed solution D.

[0158] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0159] Mixed reaction:

[0160] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0161] Powder handling:

[0162] Weigh 0.5 g of powder 1 and 0.5 g of silicon carbide powder, mix them evenly, grind them thoroughly, dissolve them in 50 ml of methanol, and continue stirring at room temperature for 2 hours to obtain a mixed solution E.

[0163] Hydrothermal reaction:

[0164] The mixed solution E was transferred to a polytetrafluoroethylene reactor and reacted at 180°C for 12 hours. The precipitate was collected by filtration using a vacuum pump and washed with DIW / methanol for 3 times. Finally, the powder 2 was obtained after vacuum drying at 60°C in a vacuum drying oven for 6 hours.

[0165] Molten salt calcination:

[0166] Weigh 0.5g of powder 2 and 0.5g of ZnCl 2 The molten salts of 1H 2 O (0.33 g) and KCl (0.17 g) were mixed evenly, ground thoroughly, and calcined in a tube furnace (temperature 950 °C, calcination time 3 h, heating rate 5 °C / min, oxygen atmosphere), then washed with deionized water 3 times, and finally dried in a vacuum drying oven at 60 °C for 24 h.

[0167] Acid leaching treatment:

[0168] The mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), and the precipitate was collected by filtration using a vacuum pump, washed with deionized water for 3 times, and finally dried in a vacuum oven at 60° C. for 6 hours to obtain the composite material of Comparative Example 5.

[0169] Comparative Example 6 (no silicon carbide, no molten salt calcination)

[0170] Experimental process:

[0171] Raw material dissolution:

[0172] Weigh 1.455 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol to obtain solution A.

[0173] Weigh 14.876 g Zn(NO 3 ) 2 6H 2 O was dissolved in 100 mL of methanol to obtain solution B.

[0174] Solutions A and B were mixed and stirred uniformly, and then 0.05 g of cetyltrimethylammonium bromide (CTAB) was added to obtain a mixed solution D.

[0175] 18.04 g of 2-methylimidazole was weighed and dissolved in 100 mL of methanol to obtain solution C.

[0176] Mixed reaction:

[0177] Solution C was added to mixed solution D, and ultrasonic stirring was performed to obtain a uniform solution (ultrasonic time was 10 min, power was 60 W). After continuous stirring at 25° C. for 24 h, the solution was centrifuged (4000 r / min), washed with methanol for 3 times, and dried (60° C., 6 h) to obtain a powder.

[0178] Powder handling:

[0179] Subsequently, the mixture was acid-leached at 80° C. for 3 hours (0.5 M HCl), the precipitate was collected by filtration using a vacuum pump, and washed three times with deionized water. Finally, the composite material of Comparative Example 6 was obtained after vacuum drying at 60° C. in a vacuum drying oven for 6 hours.

[0180] The performance tests of the composite materials obtained in the above examples and comparative examples are as follows:

[0181] Composite material catalytic test First, add 50mL of tetracycline solution with an initial concentration of 20mg / L (or 50mg / L) to the reaction tube, weigh 0.025g of the carbon-coated cobalt-based catalyst material supported by silicon carbide prepared in each embodiment and add it to the above 50mL tetracycline solution, stir continuously for 30min to reach adsorption equilibrium and test the adsorption rate. When testing the degradation rate, add 0.025g of potassium persulfate (PMS), catalyze the degradation reaction (30min), take out 3ml of solution, and immediately add methanol to quench. The concentration of the remaining tetracycline in the solution is tested by ultraviolet spectrophotometer, and the degradation rate (%) of the sample to tetracycline is calculated.

[0182] Table 1 Catalytic test results of each sample:

[0183]

[0184] The degradation and adsorption data of Example 1 and Comparative Example 1 show that the addition of silicon carbide can improve the catalytic performance and adsorption performance of the material, which is of great help to the practical use of the material.

[0185] The degradation and adsorption data of Example 1 and Comparative Examples 2-3 show that the addition of molten salt and zinc can enhance the catalytic and adsorption performances, and more importantly, the adsorption capacity.

[0186] The degradation and adsorption data of Example 1 and Comparative Example 4 show that the addition of cobalt greatly enhances the catalytic performance, and also shows that cobalt plays a major catalytic role in the material.

[0187] The degradation and adsorption data of Example 1 and Comparative Example 5 show that calcination under an inert gas atmosphere can significantly improve the catalytic degradation and adsorption performance of the material.

[0188] The degradation and adsorption data of Example 1 and Comparative Example 6 show that the addition of silicon carbide and the molten salt calcination process can enhance the catalytic and adsorption capabilities of the material.

[0189] pass Figure 1 XRD diagram shows that the carbon-coated cobalt-based catalyst material supported by silicon carbide prepared in Example 1 has Co, Co 3 C, C, SiC phases.

[0190] pass Figure 2 The TEM image shows that the silicon carbide-supported carbon-coated cobalt-based catalyst material prepared in Example 1 generates a carbon-coated structure.

[0191] pass Figure 3 The SEM image shows that the synthesis of the silicon carbide-supported carbon-coated cobalt-based catalyst material prepared in Example 1 is derived on the basis of the MOF material.

[0192] pass Figure 4 The cobalt ion leaching comparison chart shows that the cobalt leaching rate of the silicon carbide-supported carbon-coated cobalt-based catalyst material prepared in Example 1 is the lowest.

[0193] pass Figure 5 , 6 The catalytic degradation of tetracycline under different temperatures and pH conditions shows that the silicon carbide-supported carbon-coated cobalt-based catalyst material prepared in Example 1 has good stability in actual catalytic use.

[0194] The present invention shows that the carbon-coated cobalt catalyst supported by silicon carbide has better catalytic efficiency and stronger adsorption capacity than the composite catalyst synthesized by calcination without silicon carbide and molten salt. In particular, the addition of silicon carbide can stably compound cobalt on SiC, and in the long-term catalytic degradation process, it has stronger stability and higher degradation efficiency. In addition, the addition of molten salt and zinc can promote the degradation of Co. 3 The formation of C and graphite carbon forms a carbon-coated cobalt metal structure, so the generated silicon carbide-supported carbon-coated cobalt catalyst has a lower Co ion leaching rate and a higher catalytic efficiency, and the catalyst is more stable during the catalytic process. Therefore, the silicon carbide-supported carbon-coated cobalt catalyst is relatively stable under strong acid and alkali conditions and in aqueous solutions, and is also relatively stable under conditions of increased ambient temperature (25°C-65°C).

[0195] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material, characterized in that: The following steps are involved: (1) dissolving cobalt salt and zinc salt in methanol respectively, dispersing them uniformly, adding dimethyl imidazole and hexadecyl trimethyl ammonium bromide after mixing, stirring them ultrasonically at room temperature for 20 to 30 hours, maintaining the temperature of the reaction solution A at 25° C., and treating the reaction solution A to obtain a powder 1; (2) grinding the powder 1 and the alkali-etched silicon carbide powder in step (1) together, adding them into methanol, stirring them continuously at room temperature for 1 to 2 hours, and then hydrothermally reacting them at 150 to 180° C. for 10 to 12 hours, and treating the reaction liquid B to obtain powder 2; (3) The powder 2 described in step (2) is evenly mixed with a mixed molten salt of ZnCl2 and KCl in a mass ratio of 1:1, and after sufficient grinding, the mixture is heated and calcined under a protective atmosphere, and then treated with hydrochloric acid acid to obtain a carbon-coated cobalt-based composite material supported by silicon carbide.

2. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The cobalt salt is Co(NO3)2·6H2O, and the zinc salt is Zn(NO3)2·6H2O.

3. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The processing of the reaction liquid A comprises filtering the reaction liquid, washing the obtained filter cake with deionized water and methanol in sequence, and vacuum drying to obtain the powder 1.

4. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The mass ratio of the cobalt salt, the zinc salt and the dimethylimidazole is 1:10-12:12-15, and the ratio of the cobalt salt to methanol is 1g:150mL-200mL.

5. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The stirring time in step (2) is 2 hours, the temperature is 25°C, and the hydrothermal reaction time is 12 hours, the temperature is 180°C.

6. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The treatment of the reaction liquid B includes filtering the reaction liquid, washing the obtained filter cake with deionized water and methanol in sequence, and vacuum drying to obtain powder 2.

7. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The molten salt is a mixture of ZnCl2 and KCl with a mass ratio of 2:1; the mass ratio of the second powder to the molten salt is 1:

1.

8. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The protective atmosphere during the calcination process is a nitrogen atmosphere or an argon atmosphere, the heating rate is 2-5°C / min, the calcination time is 2-3 hours, and the temperature is 950-1050°C.

9. The method for preparing a silicon carbide-supported carbon-coated cobalt-based composite material according to claim 1, characterized in that: The hydrochloric acid pickling includes pickling with 0.5M hydrochloric acid at 60-80°C for 2-3 hours.

10. Use of the silicon carbide supported carbon-coated cobalt composite material prepared by the preparation method according to any one of claims 1 to 9 in treating organic pollutant wastewater, characterized in that: The silicon carbide-loaded carbon-coated cobalt-based composite material is dispersed into organic pollutant wastewater, and persulfate is added to catalytically degrade the organic pollutants, wherein the organic pollutants are one or a mixture of two or more of norfloxacin, tetracycline, and bisphenol A.